تعليم اللغة العربية للناطقين بغيرها: أبعاده الثقافية - Nasaruddin Idris Jauhar (Ulumuna, 2014)
Language and culture are closely intertwined. Language is medium through which culture is expressed. Culture consists of a set of norms or values that always use language for its expression in various forms. Speakers tend to use patterns and contexts of a language from which it originates. Experts of language argue that teaching and learning of a particular language will never be completely successful without considering cultural patterns and values of it. Cultural competency is one of the basic requirements for the study of language. From this point of view, this article attempts to formulate the concept of study of the Arabic for non-Arab students from the perspective of Islamic Arabic culture both in the contexts of Arabs and non-Arab Muslims, who study Arabic. This concept includes principles, approaches, objectives and materials of the study of Arabic as a second or foreign language.